Assessing the Impact of Autism Spectrum Disorder on School Going Children in Nairobi County: A Review of Literature - Ireri , Niceta W.; Mbwayo , Anne; Ayaa , Dominics (African Journal of Education,Science and Technology (AJEST), 2021)
Autism spectrum disorder has become a global challenge, a pervasive condition with a complex etiology impacting the lives of at least one in a hundred children across the globe. While it continues to wreck many families, for various factors the disorder is yet to be contained in Kenya, nor even Africa. In Kenya education may form part of the remedies in dealing with the affected through establishment of special schools that focus on the children with autism. Nonetheless, as the government of Kenya continues to provide a chance for children and adolescents with autism spectrum disorder (ASD)through creating a favorable school setting that may entail special classes and schools as well as mainstream schools, family functioning and their quality of life is not guaranteed. In this paper, the author conducted a review of literature on the impact of ASD on children and adolescents of school going age in schools in Nairobi County, Kenya.